Antitrust and competition convergence and divergence in the tropical mirror - Ramos, Luiz Felipe Rosa (2019)
The debate on antitrust goals is a rich, century-old dispute that seems to admit more than one approach. This thesis seeks to develop a historical-sociological approach by looking at such debate through the following question: What does it mean to protect competition as an objective of antitrust? In order to address such question, the dissertation recovers, in a first step, historical moments of the discussion and institutionalization of various antitrust goals. Although the focus is on the Brazilian case of society, even international contributions to such debate generally fail to semantically consolidate a concept of competition. It means antitrust agencies have struggled to find, in doctrine, definitions of competition that may be applicable to various decisions. In order to pursue alternative definitions, the dissertation observed how competition has been described by sociological studies. The observation of the encounters and incongruities between such \"sociology of competition\" and the emerged contributions in antitrust field has intrinsic value, that is, to illuminate the limits and latencies demarcated by antitrust when building its notions of competition. Nevertheless, the scope of the thesis is broadened by a suggestion that an approach capable of coupling sociology of competition and antitrust doctrine potentially offers a legally coherent and socially adequate concept for antitrust competition.